Synthesis and evaluation of imidazole-4,5- and pyrazine-2,3-dicarboxamides targeting dengue and yellow fever virus() - Saudi, Milind (Eur J Med Chem, 2014)
The results of a high-throughput screening assay using the dengue virus-2 replicon showed that the imidazole 4,5-dicarboxamide (I45DC) derivative (15a) has a high dengue virus inhibitory activity. Based on 15a as a lead compound, a novel class of both disubstituted I45DCs and the resembling pyrazine 2,3-dicarboxamides (P23DCs) were synthesized. Here, we report on their in vitro inhibitory activity against dengue virus (DENV) and yellow fever virus (YFV). Some of these first generation compounds have shown activity against both viruses in the micromolar range. Within this series, compound 15b was observed to display the highest antiviral potency against YFV with an EC(50) = 1.85 μM. In addition, compounds 20a and 20b both potently inhibited replication of DENV (EC(50) = 0.93 μM) in Vero cells.